The Role of Identification in Consumers' Evaluations of Brand Extensions - Marin, Longinos; Ruiz De Maya, Salvador; Rubio, Alicia (Frontiers in Psychology, 2018)
Brand extension is a widely adopted strategy for firms to take advantage of an existing brand’s equity in a new product category. The main goal of this paper is to test the moderating role consumer-company identification plays in the effect of product fit and information on consumers' evaluations of brand extensions. Study 1 demonstrates the moderator effect of identification on the effect of category fit on consumers’ purchase intentions for brand extensions and brand alliances. In Study 2, we proposed that identified consumers are not affected by information about the product, while low identified consumers rely more on that information. However, results show that the presence of information about the brand extension is only significant for identified consumers. For marketing managers, our results will help in decisions regarding extension category selection, segmentation strategy and identification cuing.